Nation and Empire Building the Iranian Way. The Case of the Sasanian Empire in the 3 rd Century - SYVÄNNE, Ilkka (Historia i Świat, 2018)
The article concentrates its attention on the practical aspects of the nation and empire building so that it: 1) Analyzes what methods, means and myths the founder Ardašīr I and his immediate successors used in the building of the Iranian nation and then the empire; 2) Provides an analysis of the importance of history and religion in the making of national myths so that the article analyzes how the Iranian leadership rewrote the past together with its religion for the purpose of uniting under their flag all those who spoke the Iranian dialects and/or practiced ancient Iranian religions, 3) Investigates what methods the Sasanians used to control the subjects; 4) Shows how the original set of falsified historical myths and the core set of religious beliefs were altered to meet the changing reality. 5) Asks whether the above provides any lessons for modernity.